PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PENGGUNA SMARTPHONE DI DESA KLAMPOKAN SITUBONDO - Desy Fitriani; Ahmad Hafas Rasyidi; Dassucik Dassucik (LPPM Politeknik Pratama, 2025)
The objectives of this study are: (1) To determine whether product quality partially affects the satisfaction of smartphone users. (2) To determine whether price partially affects the satisfaction of smartphone users. (3) To determine whether product quality and price partially and simultaneously affect the satisfaction of smartphone users in Klampokan Village, Situbondo. This study employs multiple regression analysis with the assistance of SPSS 23 software. The results indicate that the partial test (t-test) for the product quality variable (X1) and the price variable (X2) positively and significantly influences consumer satisfaction. The simultaneous test (F-test) proves that the independent variables, namely product quality (X1) and price (X2), influence the dependent variable, which is consumer satisfaction (Y).